Effects of direct moxibustion on antigen-presenting cells in gastric tissue of rat models with gastric cancer: Understanding the immunological mechanisms - Tian-yu GAO; Fei-cheng ZHANG; Ru-fang PAN; Shu-ya MA; Xiao-qi ZHANG; Li-jia PAN; Chun-sheng JIA (World Journal of Acupuncture - Moxibustion)
Objective: The preventive and therapeutic effects of direct moxibustion on a gastric cancer rat model induced by the intragastric administration of N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) were evaluated. Changes in the co-stimulatory molecules CD80 and CD86 on antigen-presenting cells in gastric tissues as well as related cytokines in serum were evaluated. The aim of the study was to explore the immunological mechanisms by which direct moxibustion may prevent gastric cancer lesions, thereby providing a basis for studies on the immunological mechanisms by which moxibustion prevents tumor development. Methods: Sixty healthy male Wistar rats were randomly divided into four groups: Control, control+moxibustion, model, and moxibustion groups. A gastric cancer rat model was induced by intragastric administration of 20 mg/mL MNNG, with a dose of 1 mL/100 g body weight, once daily for 16 weeks. The control+moxibustion and moxibustion groups received direct moxibustion simultaneously with modeling, continuing for 16 weeks. After the experiment, gastric tissue was collected, and morphological changes in the gastric mucosa in each group of rats were observed through H&E staining. Immunohistochemistry (IHC) and a western blotting were used to detect the expression levels of CD80 and CD86 in gastric tissues. Enzyme-linked immunosorbent assays (ELISA) were used to measure the levels of interleukin-12 (IL-12), interferon-gamma (IFN-γ), and tumor necrosis factor-beta (TNF-β) in rat serum. Results: Upon macroscopic observation, the gastric mucosa of rats in the control and control+moxibustion groups appeared uniformly red, with a glossy mucosal surface, normal gastric wall elasticity, and clear, regular mucosal folds, without hyperplasia or bleeding points. In the model group, the gastric mucosa was reduced in volume, the gastric wall thinned, elasticity decreased, mucosal folds were disordered, and yellow-white cauliflower-like lesions and yellow-brown hyperkeratosis were observed. In the moxibustion group, the gastric mucosa showed decreased elasticity, with disordered mucosal folds and granular hyperplasia. After H&E staining, the gastric mucosal structure was clear and intact in the control and control+moxibustion groups displaying an organized and uniform arrangement of the mucosa, submucosa, and muscularis propria, without hyperplasia or keratinization. In the model group, the epithelial glands in the gastric mucosa were disordered, with varied cell morphologies, thickened submucosa, and disrupted squamous epithelium that invaded downward into the muscularis propria. In the moxibustion group, the squamous epithelium did not invade the muscularis propria. IHC results showed higher expression levels of CD80 and CD86 in the gastric mucosa of the control+moxibustion group than in the control group (P < 0.05) and lower expression levels in the model group than in the control group (P < 0.05). The moxibustion group showed higher CD80 and CD86 levels than those in the model group (P < 0.05). Western blotting indicated that CD80 and CD86 levels were higher in the moxibustion group than in the model group (P < 0.05). ELISA results showed higher IL-12 levels in the model group than in the control group (P < 0.05) and higher TNF-β and IFN-γ levels in the moxibustion group than in the model group (P < 0.01). Conclusion: Direct moxibustion alleviates the pathological progression of gastric cancer in an MNNG-induced rat model. Its mechanisms may involve effects on the state of antigen-presenting cells, thereby promoting T cell activation and enhancing immune function.